2016
DOI: 10.4172/2329-6771.1000159
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Clinico-Pathological Characteristics of Indian Breast Cancers Shows Conservation of Specific Features in the Hormone Receptor Sub-Types

Abstract: Background: Clinical epidemiology studies of breast cancer in India have reported younger age at detection, presentation at a later stage with a greater proportion of Triple Negative Breast Cancer (TNBC). The aim of this study was to examine the standard clinic-pathological variables in the hormone-receptor based sub-types for patterns indicative of intrinsic differences from that reported in Western, Caucasian women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
2
1
0
Order By: Relevance
“…There are several studies from the Indian subcontinent regarding either HR positivity alone or HR+[ 4 8 9 18 ] and TNBCs[ 19 20 21 22 ] with only six studies delineating HER2-positive and HR-negative status as a separate category. [ 7 10 11 21 22 23 24 ] Of the latter, only one has a relatively comparable volume of 2001 cases,[ 7 ] with 16% of HER2-positive cases which is similar to the 15% found in the present study. It is worthy of note that the percentage of HER2-positive cases in the Indian subcontinent is similar to that described in the Western literature.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…There are several studies from the Indian subcontinent regarding either HR positivity alone or HR+[ 4 8 9 18 ] and TNBCs[ 19 20 21 22 ] with only six studies delineating HER2-positive and HR-negative status as a separate category. [ 7 10 11 21 22 23 24 ] Of the latter, only one has a relatively comparable volume of 2001 cases,[ 7 ] with 16% of HER2-positive cases which is similar to the 15% found in the present study. It is worthy of note that the percentage of HER2-positive cases in the Indian subcontinent is similar to that described in the Western literature.…”
Section: Discussionsupporting
confidence: 82%
“…[ 9 ] Most Indian studies to date have shown median ages ranging from 48-53 years. [ 7 8 9 10 11 ] In our study as well, the median age was 48 years, reinforcing the fact that breast cancer in Indian women occurs at least a decade younger than those in the West. [ 12 ] Most western data show a median age around 60 years.…”
Section: Discussionsupporting
confidence: 75%
“…In Indian females' breast cancer is more common in younger women which in western world. It occurs in older age group with median age of 60 years [12,[20][21][22].…”
Section: Discussionmentioning
confidence: 99%